THE EFFECT OF COLLABORATIVE LEARNING METHODS ON ELEMENTARY SCHOOL STUDENTS' ACADEMIC ACHIEVEMENT - Khairul Akbar (International Journal of Teaching and Learning, 2024)
This research aims to analyze the influence of collaborative learning methods on the academic achievement of elementary school students through a literature review from various trusted sources. The collaborative learning method is an approach that encourages interaction and collaboration between students to achieve joint learning goals. In this research, various studies discussing the effectiveness of collaborative learning methods were compiled and analyzed systematically. The results of the literature review show that there is a significant positive influence from the application of collaborative learning methods on the academic achievement of elementary school students. Some of the key findings identified include: improved understanding of subject matter, increased motivation to learn, development of social skills, better academic outcomes, and improved problem solving and critical thinking abilities. Apart from that, this research also reveals that the success of the collaborative learning method is greatly influenced by several supporting factors such as the active role of the teacher, cooperation between students, and a structured approach in its implementation. The conclusion from this literature review is that the collaborative learning method is an effective and efficient strategy in improving the academic achievement of elementary school students, and is highly recommended for integration in the basic education curriculum.